2017
DOI: 10.1111/fwb.12914
|View full text |Cite
|
Sign up to set email alerts
|

Coupling dissolved organic carbon, CO2 and productivity in boreal lakes

Abstract: Summary Lakes worldwide are in rapid change because of direct or indirect climate impacts. In boreal areas, the increased concentrations of dissolved organic matter (DOM) are profoundly affecting light climate and productivity in multiple ways. Photochemical and microbial mineralisation of DOM are major sources of CO2 in these lakes. It has been suggested that this CO2 could potentially promote primary production and offset negative impacts of increased light attenuation. A synoptic survey of 76 Scandinavian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 57 publications
(96 reference statements)
3
33
0
1
Order By: Relevance
“…Overall, in our experimental food‐web context we did not observe positive responses to CO 2 in the phytoplankton as expected from laboratory studies or others carried out with simplified plankton communities; instead, we observed either neutral effects or declines in biomass that are more in line with results from a recent cross‐lake survey (Hessen et al., ). We hypothesise that complex food‐web interactions and nutrient limitation may explain these discrepancies from simple laboratory or food‐web experiments.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Overall, in our experimental food‐web context we did not observe positive responses to CO 2 in the phytoplankton as expected from laboratory studies or others carried out with simplified plankton communities; instead, we observed either neutral effects or declines in biomass that are more in line with results from a recent cross‐lake survey (Hessen et al., ). We hypothesise that complex food‐web interactions and nutrient limitation may explain these discrepancies from simple laboratory or food‐web experiments.…”
Section: Discussionsupporting
confidence: 89%
“…In support of our observations, in a cross‐lake study, Hessen et al. () observed no effect of CO 2 on phytoplankton biomass in CO 2 ‐saturated lakes similar to ours, also a result contrasting with laboratory studies. The lack of biomass increase we observed, despite an increase in primary productivity, could be explained by a decrease in cellular Chl‐ a content after acclimation to elevated CO 2 conditions (Sobrino, Neale, Phillips‐Kress, Moeller, & Porter, ; Sobrino, Ward, & Neale, ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These references contributed to the supporting files: Aalto et al (2014), Abnizova et al (2012), Aroian (1947), Ask et al (2012), Bartoń (2015), Bartosiewicz et al (2015), Bennett et al (1999) Domysheva et al (2013Domysheva et al ( , 2010, Dunalska et al (2004), Fee et al (1996), Filzmoser and Gschwandtner (2011), Findlay et al (1999), Finlay et al (2009, Fontes et al (2015), Fraterrigo andDowning (2008), Freeman et al (2001), Fukushima et al (1996), Garcia et al (2007), Gelbrecht et al (1998), Goodman et al (2011), Gu et al (2011), Haberyan et al (2003, Hamilton et al (1994Hamilton et al ( , 1995, Heiskanen et al (2015), Hessen et al (1997Hessen et al ( , 2017, Hesslein et al (1991, 2009), Högberg et al (2001, Holgerson (2015), Hope et al (1996), Hruška et al (2003), Huttunen et al (2002), Jenson (1991), Jeppesen et al (2016), Jones and Mulholland (1998), Jones et al (2001, 2009, Kankaala et al (2013),…”
Section: References In Supporting Informationmentioning
confidence: 99%
“…found it in Lake Raslången which is farther south, on the border between Skåne and Blekinge counties. In a recent study of 75 lakes located between latitude 57-64°N from the Norwegian west coast to the Swedish east coast (Hessen et al 2017), H. borealis was not recorded in pelagic samples from any of the 31 Swedish lakes investigated (Walseng unpubl.). Other available literature does not state finds of the species in central Sweden either.…”
Section: Lake Røssvatnmentioning
confidence: 93%